Investigation of neovascularization in three-dimensional porous scaffolds in vivo by a combination of multiscale photoacoustic microscopy and optical coherence tomography. - Cai, X.; Zhang, Y.; Li, L; Choi, S. W.; Macewan, M. R.; Yao, J.; Wang, L. V.; Wang, L. V.; Li, L; Choi, S. W.; Macewan, M. R.; Yao, J.; et al.
It is a grand challenge to visualize and assess in vivo neovascularization in a three-dimensional (3D)scaffold noninvasively, together with high spatial resolution and deep penetration depth. Here we used multiscale photoacoustic microscopy (PAM), including acoustic-resolution PAM (AR-PAM)and optical-resolution PAM (OR-PAM), to chronically monitor neovascularization in an inverse opal scaffold implanted in a mouse model up to 6 weeks by taking advantage of the optical absorption contrast intrinsic to hemoglobin molecules in red blood cells. By combining with optical coherence tomography (OCT)based on optical scattering contrast, we also demonstrated the capability to simultaneously image and analyze the vasculature and the scaffold in the same mouse. The hybrid system containing OR-PAM and OCT offered a fine lateral resolution of ?5??m and a penetration depth of ?1?mm into the scaffold/tissue construct. AR-PAM further extended the penetration depth up to ?3?mm at a lateral resolution of ?45??m. By quantifying the 3D PAM data, we further examined the effect of pore size (200 vs. 80??m)of a scaffold on neovascularization. The data collected from PAM were consistent with those obtained from traditional invasive, labor-intensive histologic analyses.
Keywords: NEOVASCULARIZATION